2009
DOI: 10.21000/jasmr09010283
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF ACID MINE DRAINAGE TREATMENT USING Artemia sp. AND Allium cepa AS BIOINDICATORS OF TOXICITY AND GENOTOXICITY

Abstract: Abstract. Coal mining produces residues containing high levels of heavy metals and other components that contaminate surface and ground water. This research evaluated the efficiency of physical, chemical, and biological treatment of acid mine drainage using alternative biological indicators Artemia sp. (brine shrimp) and Allium cepa L. (onion). Samples were collected at four stations that are located at specific treatment system: 1) pH control and precipitation, 2) biological damping pond outlet, 3) wetland in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Sampling from river contaminated with industrial wastewater (mixture) MI, CA, MN MC GT, CT, MT (Srivastava et al, 2005) Contaminated water Heavy metal (Cu, As, Cd, Pb) and cyanide contaminated waters CA, NA, MI MC CT, GT (Staykova et al, 2005) Complex (Abu and Ezeugwu, 2008) www.bosaljournals/chemint/ editorci@bosaljournals.com (Carita and Marin-Morales, 2008) Lemon juice factory Composition: pH(4.46), EC(1260 uS/cm), DO (0 mg/L), T (22.4 0 C), SS (0.70 g/L), COD (42.23mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) Mining industry Composition: pH(6.12), EC(2967 uS/cm), DO (5.25 mg/L), T (23 0 C), SS (1.80 g/L), COD (23.57 mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) Sugar factory Composition: pH(4.92), EC(627 uS/cm), DO (0 mg/L), T (42 0 C), SS (0.40 g/L), COD (5566 mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) Paper factory Composition: pH(6.12), EC(4483 uS/cm), DO (0 mg/L), T (29 0 C), SS (1.80 g/L), COD (6.27 mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) River water (Bianchi et al, 2011) www.bosaljournals/chemint/ editorci@bosaljournals.com www.bosaljournals/chemint/ editorci@bosaljournals.com (Kovalchuk et al, 1998) Surface water Surface water treated with different disinfecting agent: (Monarca et al, 2003) Hospital www.bosaljournals/chemint/ editorci@bosaljournals.com (Udalova et al, 2014) www.bosaljournals/chemint/ editorci@bosaljournals.com (Aguiar et al, 2016) www.bosaljournals/chemint/ editorci@bosaljournals.com (Matsumoto and Marin-Morales, 2004) River and well water Alamuyo River in Ibadan, Nigeria and wells alongside river MI, CA MC CT, GT (Fawole et al, 2008) Radiation Roots were exposed to radiofrequency electromagnetic fields MI, CA MC CT, GT (Tkalec et al, 2009) Wastewater Un-treated and physical, chemical, and biologically treated acid mine drainage wastewater MI MC CT (Defaveri et al, 2009) Textile effluents Un-treated and treated at the absorbed doses of 5-15 kGy in combination with H2O2 RG, MI MC CT (Iqbal and Nisar, 2015) Textile (Vujošević et al, 2008) Air pollution Roots were exposed to field conditions at six research plots in the most polluted areas, Slovenia MI, CA MC CT, GT (Glasenčnik et al, 2004) Air pollution Roots were exposed at eight sampling plots in the vicinity of major Slovene local emission sources MI, CA MC CT, GT (Glasencnik et al, 2002) Contaminated soil Soil contaminated with Diuron (herbicide) MI, CA, MN MC CT, GT, MT…”
Section: Metallurgical Waste and Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling from river contaminated with industrial wastewater (mixture) MI, CA, MN MC GT, CT, MT (Srivastava et al, 2005) Contaminated water Heavy metal (Cu, As, Cd, Pb) and cyanide contaminated waters CA, NA, MI MC CT, GT (Staykova et al, 2005) Complex (Abu and Ezeugwu, 2008) www.bosaljournals/chemint/ editorci@bosaljournals.com (Carita and Marin-Morales, 2008) Lemon juice factory Composition: pH(4.46), EC(1260 uS/cm), DO (0 mg/L), T (22.4 0 C), SS (0.70 g/L), COD (42.23mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) Mining industry Composition: pH(6.12), EC(2967 uS/cm), DO (5.25 mg/L), T (23 0 C), SS (1.80 g/L), COD (23.57 mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) Sugar factory Composition: pH(4.92), EC(627 uS/cm), DO (0 mg/L), T (42 0 C), SS (0.40 g/L), COD (5566 mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) Paper factory Composition: pH(6.12), EC(4483 uS/cm), DO (0 mg/L), T (29 0 C), SS (1.80 g/L), COD (6.27 mg/L) CA, MI, MN MC MT, CT, GT (Gana et al, 2008) River water (Bianchi et al, 2011) www.bosaljournals/chemint/ editorci@bosaljournals.com www.bosaljournals/chemint/ editorci@bosaljournals.com (Kovalchuk et al, 1998) Surface water Surface water treated with different disinfecting agent: (Monarca et al, 2003) Hospital www.bosaljournals/chemint/ editorci@bosaljournals.com (Udalova et al, 2014) www.bosaljournals/chemint/ editorci@bosaljournals.com (Aguiar et al, 2016) www.bosaljournals/chemint/ editorci@bosaljournals.com (Matsumoto and Marin-Morales, 2004) River and well water Alamuyo River in Ibadan, Nigeria and wells alongside river MI, CA MC CT, GT (Fawole et al, 2008) Radiation Roots were exposed to radiofrequency electromagnetic fields MI, CA MC CT, GT (Tkalec et al, 2009) Wastewater Un-treated and physical, chemical, and biologically treated acid mine drainage wastewater MI MC CT (Defaveri et al, 2009) Textile effluents Un-treated and treated at the absorbed doses of 5-15 kGy in combination with H2O2 RG, MI MC CT (Iqbal and Nisar, 2015) Textile (Vujošević et al, 2008) Air pollution Roots were exposed to field conditions at six research plots in the most polluted areas, Slovenia MI, CA MC CT, GT (Glasenčnik et al, 2004) Air pollution Roots were exposed at eight sampling plots in the vicinity of major Slovene local emission sources MI, CA MC CT, GT (Glasencnik et al, 2002) Contaminated soil Soil contaminated with Diuron (herbicide) MI, CA, MN MC CT, GT, MT…”
Section: Metallurgical Waste and Metalsmentioning
confidence: 99%
“…Treatment of AMD with calcinated sediment reduced the acidity and metals, which in trun showed less toxic and genotoxic effects. Similarly, Defaveri et al (2009) evaluated the efficiency of physical, chemical, and biological treatment of acid mine drainage using alternative biological indicator A. cepa. Samples were collected at four stations that are located at specific treatment system: 1) pH control and precipitation, 2) biological damping pond outlet, 3) wetland inlet, and 4) wetland outlet.…”
mentioning
confidence: 99%
“…Comet assay was also used to evaluate the efficiency of new treatment technology to decrease acid mine drainage genotoxicity. Defaveri et al ( 2009 ) and Netto et al ( 2013 ) used A. cepa roots, and different biomarkers including DNA damages and other cytotoxic and physiological biomarkers, while Radić et al ( 2010 ) used the aquatic species Lemna minor . In a previous study, these authors demonstrated in Lemna minor that the tail moment assessed by the plant comet assay and parameters related to oxidation were suitable as biomarkers for environmental monitoring of the toxicity of industrial effluents in Croatia (Radić et al, 2010 ).…”
Section: Contaminated Matricesmentioning
confidence: 99%